Uncovering the new landscape of leukoaraiosis through the circular RNA-miRNA-mRNA axis - Zhu, Canmin; Chang, Chang; Jin, Qiangjian; Xu, Xi; Pang, Weili; Fang, Yang; Yang, Ting; Jin, Lanying; Wang, Dili (Frontiers in Neurology, 2025)
BackgroundWhite matter disease arises from the loss of oligodendrocyte progenitor cells and is associated with adverse outcomes in leukoaraiosis (LA) patients. Although the regulatory roles of circ-RNA/miRNA/mRNA in brain disorders are well-documented, their impact and mechanisms in white matter injury (WMI) remain unclear. This study aimed to investigate the involvement of hsa_circ_0018401/miR-145-5p/AIFM1 axis in white matter injury.MethodWhole blood samples from LA patients underwent quantitative real-time polymerase chain reaction (qRT-PCR) to evaluate the expression levels of circular RNA and miRNA. Bioinformatics tools were employed to predict the downstream miRNA. Primary oligodendrocyte progenitor cells (OPCs) were isolated from rats. The downstream miRNA, miR-145-5p, of circ-0018401 in OPCs was confirmed through Luciferase gene assays and qRT-PCR. Luciferase gene assays were also used to explore the interaction between miR-145-5p and AIFM1 in OPCs and HEK-293T cells. Western blotting and qRT-PCR were utilized to analyze the expression levels of AIFM1 in OPCs overexpressing miR-145-5p.ResultsElevated levels of circ-0018401 were observed in the whole blood of patients with white matter injury. Overexpression of circ-0018401 resulted in decreased levels of miR-145-5p in OPCs. Luciferase gene assays and qPCR verified the binding of circ-0018401 with miR-145-5p in OPCs. The apoptotic gene AIFM1 was identified as a downstream target of miR-145-5p.Conclusioncirc-0018401 acts as a crucial biomarker in white matter injury by regulating the miR-145-5p/AIFM1 axis. This research opens up a new path for the development of therapeutic strategies for white matter injury.